Programa de Habilidades Sociales y su influencia en las Relaciones Interpersonales de los estudiantes del 1er grado, nivel Secundaria, Institucin Educativa N 80129 Virgen del Carmen, Trujillo, ao 2015 - Cruz Laiza, Hilver Breiner (2017)
The present research work entitled: Social Skills Program and its influence on the Interpersonal Relations of the students of the 1st grade, secondary level, educational institution n 80129 "Virgen del Carmen", Trujillo, year 2015, had the purpose of identifying the relationship Of the Social Skills and Interpersonal Relations Program of the students._x000D_ _x000D_ For this study, the method of simple random sampling was applied, taking as sample 30 students of the first grade of the secondary level of the educational institution. This work, besides serving for other investigations of such magnitude, proposes a program of theoretical and practical Social Skills, with methodological strategies to improve Interpersonal Relations with the Other._x000D_ _x000D_ To measure the level of Interpersonal Relations, a 20-item Interpersonal Relations instrument was developed and structured in the family, school and student society. Regarding the level of interrelation, a total percentage was obtained in the three dimensions, located within the levels: bad, regular and good. Therefore, it has been concluded that there is a significant positive relationship between the social skills program and the interpersonal relationships of students. In addition it was achieved that 100% of the students located in a good level of relation with the Other